2017
DOI: 10.1002/2016ja023523
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide nightglow and Martian mesospheric circulation from MAVEN/IUVS observations and LMD‐MGCM predictions

Abstract: We report results from a study of nitric oxide nightglow over the northern hemisphere of Mars during winter, the southern hemisphere during fall equinox, and equatorial latitudes during summer in the northern hemisphere based on observations of the δ and γ bands between 190 and 270 nm by the Imaging UltraViolet Spectrograph (IUVS) on the Mars Atmosphere and Volatile EvolutioN mission (MAVEN) spacecraft. The emission reveals recombination of N and O atoms dissociated on the dayside of Mars and transported to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 49 publications
3
14
0
Order By: Relevance
“…longitudinal variability of thermal structure in the middle atmosphere. Longitudinal variations of nitric oxide (NO) nightglow reported by Stiepen et al (2017) show a comparable signature, which seems to be in phase with those found in this study. These waves apparently have an impact on the amplitude of the warm layer.…”
Section: 1029/2019gl085646supporting
confidence: 86%
“…longitudinal variability of thermal structure in the middle atmosphere. Longitudinal variations of nitric oxide (NO) nightglow reported by Stiepen et al (2017) show a comparable signature, which seems to be in phase with those found in this study. These waves apparently have an impact on the amplitude of the warm layer.…”
Section: 1029/2019gl085646supporting
confidence: 86%
“…The NO dayglow is a direct measure of NO densities in the Martian upper atmosphere. This is in contrast to the NO nightglow, which has been reported using MUV limb observations from several instruments (Bertaux et al, 2005;Cox et al, 2008;Gagné et al, 2013;Stiepen et al, 2015Stiepen et al, , 2017. The NO nightglow is excited chemically by the radiative recombination of nitrogen and oxygen atoms and therefore provides no direct information on NO densities.…”
Section: The Maven/iuvs Dayglow Observationsmentioning
confidence: 73%
“…NO was observed in the upper atmosphere by Mars Express (Gagné et al, 2013) and Mars Atmosphere and Volatile EvolutioN Mission (Stiepen et al, 2017). NO and N form in the thermosphere through N 2 photodissociation in the wavelength from 80 to 100 nm, photoelectron impact dissociation of N 2 , recombination of N 2 + and NO + , the reaction of N 2 + with O, and the reaction of O + ( 2 P) with N 2 (Smith et al, 2014;Yung et al, 1977).…”
Section: Comparison With Other Energy Sourcesmentioning
confidence: 99%